Mechanical structural component and method for producing same
By adjusting the steel composition and manufacturing conditions, the original austenite grain size and area ratio in the hardened layer are ensured, combined with the appropriate rolling speed and high-frequency heat treatment temperature, the problem of large strain of mechanical structural components after high-frequency heat treatment is solved. , achieving low strain and low eccentricity effects, reducing production costs.
Patent Information
- Application Number
- CN202380030357.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-27
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art After high-frequency heat treatment, there are major strain problems in mechanical structural components, especially shaft-shaped components, which lead to eccentricity and cost increase. The existing methods mainly focus on reducing carburizing heat treatment strain, but are not sufficient to reduce high-frequency heat treatment. strain.
By adjusting the steel composition and manufacturing conditions, ensure that the particle size of the original austenite grain in the hardened layer is less than 80 μm, the area ratio reaches more than 80%, and the proportion of the number of grains with a maximum frequency of the particle size is controlled. Below 5%, combined with appropriate rolling speed and high-frequency heat treatment temperature, low-strain mechanical structural components are formed.
It effectively reduces the strain after high-frequency heat treatment, suppresses the eccentricity of mechanical structural components, reduces production costs, and improves the mechanical characteristics and fatigue strength of the components.
Smart Images

Figure CN119213155A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a machine structural component having a hardened layer formed by high-frequency quenching and tempering, particularly a machine structural component having a shaft-shaped portion, and a method for manufacturing the same, which is used in the fields of construction industry machinery and automobiles. Background Art
[0002] Power transmission parts such as drive shafts and half shafts used in automobiles, engineering machinery, etc. use alloy steel for mechanical structures, such as SCr420 and SCM420 according to the JIS standard. The outline of the manufacturing method of such parts is as follows. That is, the bar steel and wire rod made of alloy steel for mechanical structures as the blank are roughly formed into the shape of the parts by hot forging and / or cold forging, and fine forming is performed by cutting. Then, surface hardening treatments such as high-frequency quenching and tempering (high-frequency heat treatment) and carburizing quenching and tempering (carburizing heat treatment) are implemented to make the product. High-frequency heat treatment and carburizing heat treatment harden the object parts by heating and maintaining at above 900°C and then cooling, using the phase change of the steel structure. Therefore, heat treatment strain caused by the phase change of the steel structure is generated during heating. In particular, in parts with a large aspect ratio of the shaft-shaped part such as shafts, the eccentricity of the parts caused by the strain cannot be ignored, and a correction process corresponding to its degree is required, which leads to increased costs.
[0003] To address such problems, for example, technologies described in Patent Documents 1 to 5 have been proposed. Specifically, Patent Document 1 proposes a method for producing steel in which coarsening of austenite grains is suppressed by precipitating AlN to reduce heat treatment strain during carburizing heat treatment.
[0004] Patent Document 2 proposes to control the cooling rate within a predetermined temperature range after hot working to control the size and precipitation density of AlN and reduce the heat treatment strain during carburizing heat treatment.
[0005] Patent Document 3 proposes a steel and a method for producing the steel in which decarburization is reduced and the generation of coarse grains and heat treatment strain during carburizing heat treatment are reduced by controlling the heating and hot rolling temperatures after casting.
[0006] Patent Document 4 proposes a steel and a method for producing the steel in which the generation of coarse grains and heat treatment strain during carburizing heat treatment are reduced by controlling the precipitation of TiN due to Ti addition and the finishing temperature of hot rolling.
[0007] Patent Document 5 proposes to control the deviation of the martensitic transformation point in the cross section perpendicular to the long side of the steel bar to suppress the occurrence of non-uniform martensitic transformation and reduce the heat treatment strain generated during carburizing and quenching or carbonitriding and quenching.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 61-261427
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 8-199316
[0012] Patent Document 3: Japanese Patent Application Publication No. 2004-204263
[0013] Patent Document 4: Japanese Patent Application Publication No. 2006-265703
[0014] Patent Document 5: Japanese Patent Application Publication No. 2013-151719 Summary of the invention
[0015] Here, comparing carburizing heat treatment and high-frequency heat treatment, carburizing heat treatment generates a larger strain after heat treatment. Therefore, in the past, the focus was placed on reducing the strain after carburizing heat treatment. Therefore, although the techniques shown in Patent Documents 1 to 5 are effective in reducing the strain generated by carburizing heat treatment, they are not sufficient to reduce the smaller strain generated by high-frequency heat treatment.
[0016] The present invention has been developed in view of the above-mentioned actual situation, and its object is to provide a mechanical structural component and a manufacturing method thereof that solves the eccentricity problem of a component having a large aspect ratio of a shaft-shaped portion by reducing strain after high-frequency heat treatment.
[0017] The inventors investigated the influence of steel composition and steel manufacturing conditions on the strain after high-frequency heat treatment in order to reduce the strain of parts after high-frequency heat treatment. As a result, they found that the following (a) and (b) are important for reducing the strain after high-frequency heat treatment.
[0018] (a) To reduce the variation in the grain size of prior austenite grains in the hardened layer after high-frequency heat treatment. (b) To make prior austenite grains with a small grain size occupy a large area in the hardened layer after high-frequency heat treatment.
[0019] The present invention has been accomplished based on the above findings, and its gist is as follows.
[0020] 1. A mechanical structural component having the following composition, which contains, by mass%, C: 0.45-0.51%, Si: 0.15-0.35%, Mn: 0.60-0.90%, P: 0.030% or less, S: 0.025% or less, Al: 0.040-0.059%, Cr: 0.10-0.50% and N: 0.0060-0.0100%, and the remainder is Fe and impurities; having a hardened layer formed by high-frequency quenching and tempering treatment; the area ratio of the grains with a grain size of 80 μm or less of the original austenite grains in the hardened layer is 80% or more, and the number ratio of the grains with a grain size of more than twice the grain size mode in the hardened layer is 5% or less.
[0021] 2. The mechanical structural component according to item 1 above, wherein the component is a component having a shaft-shaped portion.
[0022] 3. A method for manufacturing a mechanical structural component, comprising hot rolling a steel billet having the following composition, at a rolling speed VSL satisfying the following formula (1), to produce a steel bar or a wire rod, forging the steel bar or the wire rod, and then subjecting the steel bar or the wire rod to high-frequency quenching and tempering at 900 to 1150° C., wherein the composition comprises, in mass %, C: 0.45 to 0.51%, Si: 0.15 to 0.35%, Mn: 0.60 to 0.90%, P: 0.030% or less, S: 0.025% or less, Al: 0.040 to 0.059%, Cr: 0.10 to 0.50% and N: 0.0060 to 0.0100%, with the remainder being Fe and impurities.
[0023] VSL≤100 / DL(m / s)···(1)
[0024] Wherein, VSL is the rolling speed (m / s) just before passing through the final stage of rolling, and DL is the diameter of the rolled material after the rolling is completed (mm).
[0025] According to the present invention, a mechanical structural component with low residual strain can be provided. In particular, since the strain is reduced in the mechanical structural component having the shaft-shaped portion, the eccentricity of the mechanical structural component can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a graph showing the correlation between the area ratio of prior austenite grains having a grain size of 80 μm or less in the hardened layer and the core runout (eccentricity). DETAILED DESCRIPTION
[0027] Hereinafter, one embodiment of the present invention will be described in detail starting from the chemical composition of the steel used for the machine structural component of the present invention. It should be noted that "%" indicating the content of each element means "mass %" unless otherwise specified.
[0028] C: 0.45~0.51%
[0029] C is an element necessary to ensure the strength of the hardened layer of the component when high-frequency heat treatment is performed. When the C content is less than 0.45%, the strength of the component is insufficient. On the other hand, if the C content exceeds 0.51%, the strain after high-frequency heat treatment increases. Based on the above reasons, the C content is specified to be in the range of 0.45 to 0.51%. From the viewpoint of balancing the strength and the strain, it is preferred that the C content be 0.47% or more. Similarly, it is preferably 0.49% or less.
[0030] Si: 0.15~0.35%
[0031] Si has the effect of reducing oxygen inclusions by deoxidizing steel and suppressing the hardness reduction during tempering heat treatment. That is, it has the effect of improving the mechanical properties of the product. On the other hand, if excessively added, the cold workability is reduced due to the hardening of the blank. For the above reasons, the Si content is specified to be in the range of 0.15 to 0.35%. A more preferred range is 0.20% or more. A more preferred range is 0.30% or less.
[0032] Mn: 0.60~0.90%
[0033] Mn has the effect of greatly improving hardenability, so it is necessary to add 0.60% or more. On the other hand, as the amount of addition increases, the hardness of the blank increases and the cold workability decreases, but a maximum of 0.90% is allowed. Based on the above reasons, the Mn content is specified to be in the range of 0.60 to 0.90%. It should be noted that a more preferred range is 0.70% or more. A more preferred range is 0.80% or less.
[0034] P: 0.030% or less (including 0%)
[0035] P has the effect of segregating at the grain boundaries of the original austenite after high-frequency quenching and reducing the fatigue properties of the hardened layer. Therefore, it is preferred to suppress the P content to a small amount as much as possible. Based on the above reasons, the P content is specified to be within the range of 0.030% or less. It should be noted that it is more preferably suppressed to 0.012% or less. Of course, it can also be 0%.
[0036] S: 0.025% or less (including 0%)
[0037] S exists in the form of sulfur inclusions and is an effective element for improving machinability. However, addition of more than 0.025% has an adverse effect on manufacturability during casting, so the upper limit is 0.025%. It should be noted that when it is necessary to improve machinability, 0.010% or more can be added, preferably in the range of 0.010 to 0.015%. It should be noted that when machinability is not necessary, 0% can be added.
[0038] Al: 0.040~0.059%
[0039] Al combines with N to form AlN, so it has the effect of suppressing the coarsening of austenite grains during rolling of steel bars and wires and high-frequency quenching. Controlling the austenite grain size during rolling of steel bars and wires and high-frequency quenching is effective for suppressing strain, so it is an important element in the present invention. When the Al content is low, the above effect cannot be expected. On the other hand, when the Al content is excessive, it leads to an increase in inclusions, increases the starting point of fatigue failure, and becomes a cause of reduced fatigue strength. Based on the above reasons, the Al content is specified to be in the range of 0.040 to 0.059%. Preferably 0.045% or more. Preferably 0.055% or less.
[0040] Cr: 0.10~0.50%
[0041] Cr effectively improves the hardenability and strength of steel. On the other hand, if the Cr content increases, the workability will inevitably decrease due to the increase in hardness. Based on the above reasons, the Cr content is set to a range of 0.10 to 0.50%. Preferably, it is 0.10% or more. Preferably, it is 0.20% or less.
[0042] N: 0.0060~0.0100%
[0043] N combines with Al to form AlN, and is therefore an important element in the present invention like Al. In order to control the austenite grain size during bar and wire rolling and high-frequency quenching, it is necessary to contain 0.0060% or more of N. On the other hand, if the N content increases, cracks will occur during solidification, and will remain as defects in subsequent processes. If the defect still remains, the defect will open and cracks will easily occur significantly, so it cannot be used as a product. Based on the above reasons, the N content is specified to be in the range of 0.0060 to 0.0100%. Preferably, it is 0.0060% or more. Preferably, it is 0.0080% or less.
[0044] In the mechanical structural component of the present invention, the remainder of the composition includes Fe and impurities. Impurities are impurities mixed from raw materials such as ore, waste or manufacturing environment during industrial steel production, and are allowed within the range that does not adversely affect the characteristics of this embodiment.
[0045] Next, the definition of the prior austenite grain size of the hardened layer formed by the high-frequency heat treatment in the present invention will be described.
[0046] The mechanical structural part of the present invention uses the steel of the above composition, is formed into a part shape such as a shaft shape, and then subjected to high-frequency heat treatment of high-frequency quenching and tempering. In the hardened layer formed by the high-frequency heat treatment, the area ratio of the grains with a grain size of 80 μm or less of the original austenite grains must be 80% or more, and the number ratio of the grains with a grain size of more than twice the grain size mode must be 5% or less.
[0047] [Hardened layer]
[0048] In the mechanical structural component of the present invention, a high-frequency heat treatment of high-frequency quenching and tempering is performed on the molded body in the shape of the component to form a hardened layer on the surface. The hardened layer is a portion hardened by high-frequency heat treatment. Specifically, the hardness (e.g., Vickers hardness) distribution is measured from the surface of the component after high-frequency heat treatment to the center, and the depth position at which the specified hardness (e.g., HV450) is maintained in the obtained hardness distribution is set as the effective hardened layer depth (ECD), and the area of the effective hardened layer depth is set as the hardened layer.
[0049] [The area ratio of the prior austenite grains having a grain size of 80 μm or less is 80% or more]
[0050] The regulation of the prior austenite grain size is an indicator of the properties of the prior austenite grains that can suppress the strain after high-frequency heat treatment. Here, the relationship between the area ratio of the prior austenite grains with a grain size of 80 μm or less and the core runout (if it is 0.25% or less, the strain in the component is suppressed) in the examples described later is as follows: Figure 1 As shown, when the area ratio of the grains with a grain size of 80 μm or less of the original austenite grains meets 80% or more, the core swing can be effectively suppressed, that is, the strain in the component can be suppressed. It should be noted that the grains with a grain size of 80 μm or less of the original austenite grains are restricted because the original austenite grains with a grain size greater than 80 μm have a great influence on the suppression of the core swing. By restricting the grains exceeding 80 μm, the desired core swing suppression capability can be obtained. Therefore, the area ratio of the grains with a grain size of more than 80 μm of the original austenite grains is less than 20%. In other words, the area ratio of the grains with a grain size of 80 μm or less of the original austenite grains is 80% or more.
[0051] Here, the original austenite grain size can be obtained by appropriately corroding and observing the parts after high-frequency heat treatment. For example, after the hardened layer formed on the surface of the part is corroded with a picric acid solution to make the original austenite grain boundary visible, the original austenite grain structure can be photographed and processed using image processing software to obtain the equivalent circle diameter of each original austenite grain, and the area ratio of grains below 80 μm can be calculated.
[0052] [The number ratio of crystal grains having a grain size that is twice or more the grain size mode is 5% or less]
[0053] By making the number ratio of grains with a grain size of more than 2 times the grain size mode value in the hardened layer less than 5%, the strain and eccentricity of the parts after high-frequency quenching can be suppressed. Even if the area ratio of the original austenite grains in the previous item is met, if a certain small number of original austenite grains are significantly coarsened than other grains (specifically, more than 2 times the grain size mode value), the eccentricity suppression cannot reach the desired level. In this way, it is found that the above conditions are suitable as a standard for suppressing eccentricity.
[0054] Here, the particle size mode can be obtained by appropriately corroding and observing the parts after high-frequency heat treatment. For example, it can be obtained by a particle size histogram, which is obtained by corroding the hardened layer formed on the surface of the part with a picric acid solution to make the original austenite grain boundary visible, photographing the original austenite grain structure, and processing it using image processing software. Furthermore, the number ratio of grains with this particle size can be obtained from the histogram.
[0055] Next, a method for manufacturing a machine structural component according to the present invention will be described.
[0056] That is, a steel billet having the above-mentioned composition is hot rolled at a rolling speed satisfying the following formula (1) to produce a steel bar or a wire rod, the steel bar or wire rod is forged into a component shape, and then subjected to high-frequency quenching at 900 to 1150° C. to produce a mechanical structural component. It should be noted that the steel billet is not particularly limited to a cast piece, for example, a billet as a typical example, or a slab.
[0057] Here, in order to satisfy the above-mentioned requirements on the grain size of prior austenite in the hardened layer, in addition to adjusting the above-mentioned component composition, it is necessary to hot-roll the steel billet, such as the cast sheet, at a rolling speed satisfying the following formula (1) to produce a steel bar or wire.
[0058] VSL≤100 / DL(m / s)···(1)
[0059] Wherein, VSL is the rolling speed (m / s) just before passing through the final stage of rolling, and DL is the diameter of the rolled material after the rolling is completed (mm).
[0060] The above formula (1) is an index of the rolling speed when the cast sheet is hot rolled into a steel bar or wire rod as a forging billet for making mechanical structural parts. By setting an appropriate rolling speed according to the diameter of the steel bar or wire rod, the temperature gradient inside the rolled material can be reduced and the structure of the rolled material can be controlled. By adopting a rolling speed that satisfies this formula, the time required for cooling inside the rolled material can be ensured, and the temperature difference between the surface and the inside of the rolled material can be suppressed, resulting in a uniform structure after rolling. Therefore, when the rolling speed and the diameter of the rolled material do not satisfy the above formula (1), even if the heat treatment conditions during the high-frequency heat treatment described later are met, the original austenite grain size in the final component cannot meet the above conditions.
[0061] Furthermore, from the viewpoint of suppressing strain, it is preferable to adopt a rolling speed that sets the constant on the right side of the formula (1) to 100 to 90. That is, hot rolling at a rolling speed that satisfies the following formula (2) is suitable for suppressing strain.
[0062] VSL≤90 / DL(m / s)···(2)
[0063] Wherein, VSL is the rolling speed (m / s) just before passing through the final stage of rolling, and DL is the diameter of the rolled material after the rolling is completed (mm).
[0064] By the way, it is appropriate to use the diameter of the rolled material just before the final stage of rolling as an indicator of the rolling speed, but the final stage of rolling of bars or wires is usually a slight reduction for sizing, and the change in diameter is small, so the diameter after rolling is completed can be used.
[0065] The steel bar or wire manufactured as described above is processed by hot forging and / or cold forging, cutting, etc. to be finished into a component shape, and then subjected to high-frequency heat treatment to become a component. In order to make the original austenite grains of the hardened layer after high-frequency heat treatment meet the above-mentioned grain size conditions, the high-frequency quenching temperature must be 900-1150°C.
[0066] The above temperature range is defined based on the following: within the range of the composition of the present invention, complete austenite transformation occurs during heating and no significant austenite grain growth occurs during heating. It should be noted that the tempering heat treatment after high-frequency quenching may be performed under known conditions.
[0067] Example
[0068] Hereinafter, the constitution and effects of the present invention will be described in more detail according to the embodiments. However, the present invention is not limited to the following embodiments, and may be appropriately modified within the scope suitable for the gist of the present invention, and these are all included in the technical scope of the present invention.
[0069] The steel with the composition shown in Table 1 is melted and made into a cast sheet by continuous casting, which is processed into a billet and then hot-rolled into round bars of various diameters. The hot rolling conditions are that the diameter of the rolled material after rolling is DL=30mm and the rolling speed VSL=3.0m / s just before passing through the final section of rolling. The properties required for steel for mechanical structures were investigated for the obtained round bars. The hardness of the round bars after hot rolling is measured as the property required for steel for mechanical structures, that is, the property of the steel itself, and then the hardness distribution of the round bars after the high-frequency heat treatment described later is measured as an evaluation of hardenability.
[0070]
[0071] In the hardness measurement, the Vickers hardness is measured at a depth of 300 gf from the circumference of the round bar to 1 / 4 of the diameter of the round bar. Measurements are performed at any 10 points, and the average value is calculated for evaluation. As the Vickers hardness here, from the viewpoint of cold workability, it is preferably HV195 or less.
[0072] The hardness distribution measurement after high-frequency heat treatment is carried out by high-frequency heat treatment of the round rod. The high-frequency heat treatment is carried out at a frequency of 8.5kHz, a maximum heating temperature of 1000°C, and mobile quenching. Tempering is carried out using a heating furnace at 180°C and 30 minutes. Then, the Vickers hardness measurement is carried out at 300gf from the surface to the center of the axial perpendicular section of the round rod. That is, the depth position of 1mm radially inward from the surface of the round rod is set as the first point, and then the radial hardness distribution is evaluated at a spacing of 1mm to the radial inside. Based on the result, the layer from the surface to the position above HV450 is evaluated as the effective hardened layer depth (ECD). The effective hardened layer depth region is the hardened layer of the present invention. In order to ensure the strength of the component, it is preferred that the ECD is more than 10% of the diameter of the round rod.
[0073] Table 2 shows these measurement results.
[0074] [Table 2]
[0075]
[0076] Furthermore, using the same castings as those used in the above-mentioned hardness measurement and hardness distribution measurement, billets produced from each casting were subjected to hot rolling and high-frequency quenching heat treatment under the component manufacturing conditions shown in Table 3 to produce shaft components. It should be noted that the component shape is a round bar obtained by extrusion processing with a reduction rate of 20% from a hot-rolled steel bar, and the high-frequency heat treatment was performed after adjusting the conditions so that the ECD (i.e., the thickness of the hardened layer) becomes about 10% of the shaft diameter.
[0077] The number ratio of grains having a grain size of twice or more the grain size mode and the area ratio of prior austenite grains having a grain size of 80 μm or less in the hardened layer of the obtained component were examined.
[0078] [Ratio of the number of crystal grains having a grain size twice or more of the grain size mode]
[0079] The observation of the original austenite grains in the hardened layer of the component is carried out by cutting out a sample with the axial vertical section of the above-mentioned shaft component as the observation surface. The cut sample is corroded with a 3% picric acid aqueous solution, and the original austenite grain structure of 10 fields of view is photographed at 200 times at half the position of the ECD using an optical microscope. Based on the photographs, the original austenite grain boundaries are tracked, and the tracking images are processed using the image processing software ImageJ. The diameter of each original austenite grain is calculated and rounded to an integer as the equivalent circle diameter. Based on the obtained particle size data, the particle size with the largest number of grains is defined as the most frequent value, and the ratio of the number of grains greater than twice the most frequent value to the total number of grains is calculated. It should be noted that when there are multiple candidates for the most frequent value, the smallest one will be treated as the most frequent value.
[0080] [Area ratio of prior austenite grains having a grain size of 80 μm or less]
[0081] The area ratio of prior austenite grains having a grain size of 80 μm or less was calculated by performing image analysis on the tracking image obtained in the same manner as above.
[0082] Furthermore, the obtained parts were evaluated for torsional fatigue life and part core runout.
[0083] [Torsional fatigue life]
[0084] Torsion fatigue life was measured using an electric servo torsion fatigue testing machine. The load was 2 Hz and the maximum shear stress was 300 MPa, and the number of repetitions until failure was measured. When the failure life was more than 15,000 times in this test, it can be said that the fatigue strength was sufficient.
[0085] [Component core runout]
[0086] The strain of the component is measured using an eccentricity inspection machine. That is, the core runout (%) is calculated by dividing the range of displacement variation (the difference between the maximum displacement and the minimum displacement) when the component is rotated once by supporting the holes drilled at the center of both ends before high-frequency heat treatment by the diameter of the measured part. In this test, if the core runout is less than 0.25%, it can be said that the strain of the component is sufficiently suppressed.
[0087] The obtained evaluation results are shown in Table 3. Figure 1The relationship between the area ratio of prior austenite grains with a grain size of 80 μm or less and the core runout is summarized. It should be noted that the figure only shows examples where the fatigue life is within the preferred range.
[0088] [Table 3]
[0089]
[0090] ※“E+04” in torsional fatigue life means “×10 4 ”.
Claims
1. A mechanical structural component having the following composition, which contains, by mass%, C: 0.45-0.51%, Si: 0.15-0.35%, Mn: 0.60-0.90%, P: 0.030% or less, S: 0.025% or less, Al: 0.040-0.059%, Cr: 0.10-0.50% and N: 0.0060-0.0100%, and the remainder is Fe and impurities; having a hardened layer formed by high-frequency quenching and tempering treatment; the area ratio of the grains with a grain size of 80 μm or less of the original austenite grains in the hardened layer is 80% or more, and the number ratio of the grains with a grain size of more than twice the grain size mode in the hardened layer is 5% or less.
2. The mechanical structural component according to claim 1, wherein: The member is a member having a shaft-shaped portion.
3. A method for manufacturing a mechanical structural component, comprising hot rolling a steel billet having the following composition at a rolling speed VSL satisfying the following formula (1) to produce a steel bar or a wire rod, forging the steel bar or the wire rod, and then subjecting the steel bar or the wire rod to high-frequency quenching and tempering at 900 to 1150° C., wherein the composition comprises, in mass %, C: 0.45 to 0.51%, Si: 0.15 to 0.35%, Mn: 0.60 to 0.90%, P: 0.030% or less, S: 0.025% or less, Al: 0.040 to 0.059%, Cr: 0.10 to 0.50% and N: 0.0060 to 0.0100%, and the remainder is Fe and impurities; VSL≤100 / DL(m / s)···(1) in, VSL is the rolling speed just before passing through the final rolling section, in m / s, and DL is the diameter of the rolled material after rolling is completed, in mm.
